[Faculty and students dressed in costumes] (1937)
This was probably a photo of Cal Poly staff putting on a show for the students on February 26, 1937. The photo includes the staff dressed up in costumes, two of them in blackface. The photo appears in the 1937 El Rodeo yearbook.